GUARANTEES OF THE PROTECTION OF PROFESSIONAL SECRETS DURING THE INTERROGATION OF A WITNESS IN ADMINISTRATIVE JURISDICTION - Денисенко, Г. В. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2023)
Abstract. The article examines the guarantees of protection and confidentiality of information entrusted to lawyers, clergy, judges, jurors, persons with diplomatic immunity and representatives of diplomatic missions in connection with the exercise of their professional powers during their interrogation as witnesses. in administrative proceedings. The article highlights the issue of compliance with administrative-procedural guarantees of protection of information constituting professional secrets, reveals the meaning and essence of the guarantees of secrets through the implementation by persons who cannot be questioned as witnesses of immunity in administrative proceedings. The purpose of the article is to determine the unity of approaches to understanding the guarantees of protection of professional secrets and procedural immunity to lawyers, clergymen, judges, jurors, persons who have diplomatic immunity and representatives of diplomatic missions in connection with their exercise of their professional powers, during their interrogation as witnesses in administrative proceedings. On the basis of the analysis of the provisions of the Code of Administrative Procedure of Ukraine, the research of scientists and materials of practice, a unity was formed to understand the concept of the right of a lawyer, a clergyman, a judge, a juror, persons with diplomatic immunity and representatives of diplomatic missions to implement a procedural guarantee of protection in the form of a legal prohibition to be questioned as a witness in administrative proceedings.

Анотація. У статті досліджено гарантії охорони та збереження у таємниці відомостей, що були довірені адвокатам, священнослужителям, суддям, присяжним, особам, які мають дипломатичний імунітет та представникам дипломатичних представництв у зв’язку із реалізацією ними своїх професійних повноважень, під час їх допиту як свідків у адміністративному судочинстві. У статті висвітлено питання дотримання адміністративно-процесуальних гарантій охорони відомостей, що становлять професійні таємниці, розкрито зміст поняття та сутності гарантій таємниць через реалізацію особами, які не можуть бути допитані як свідки імунітету в адміністративному судочинстві. Метою статті є визначення єдності підходів до розуміння гарантій охорони професійних таємниць та процесуального імунітету адвокатам, священнослужителям, суддям, присяжним, особам, які мають дипломатичний імунітет, та представникам дипломатичних представництв у зв’язку із реалізацією ними своїх професійних повноважень, під час їх допиту як свідків у адміністративному судочинстві. На підставі аналізу положень Кодексу адміністративного судочинства України, досліджень науковців та матеріалів практики сформовано єдність щодо розуміння поняття права адвоката, священнослужителя, судді, присяжного, осіб, які мають дипломатичний імунітет, та представників дипломатичних представництв реалізувати процесуальні гарантії охорони у формі законодавчої заборони бути допитаними як свідки в адміністративному судочинстві.
ГАРАНТІЇ ОХОРОНИ ПРОФЕСІЙНИХ ТАЄМНИЦЬ ПІД ЧАС ДОПИТУ СВІДКА В АДМІНІСТРАТИВНОМУ СУДОЧИНСТВІ
Keywords: guarantees of protection of secrets; secrets; information constituting a secret protected by law; evidence; proof; admissibility of evidence; secret; administrative proceedings; administrative process; lawyer; lawyer’s secret; priest; judge; juror; secret confession of believers; witness immunity; witness; diplomatic immunity; interrogation.; гарантії охорони таємниць; таємниця; докази; доказування; допустимість доказів; адміністративне судочинство; адвокат; адвокатська таємниця; священнослужитель; суддя; присяжний; таємниця сповіді віруючих; імунітет свідка; свідок; допит.